Photography, ecology and historical change in the anthropocene - Arends, Bergit, author.
1 online resource.
Keywords: "Moving beyond existing scholarship, this book connects photography, archives, ecology, and historical change, and critically applies the Anthropocene as framework to the in-depth study of artists' projects. It discards single modes of seeing environmental transformations in favour of a multiple and de-centred environmental imagination. Bergit Arends uses multi-disciplinary perspectives to view localised environmental, social, and political issues through research-based artistic practices. The book not only makes available original research into newly and recently discovered archives of ecological and historical change, but also shows how this research is manifest in exhibition formats. This book presents international, transhistorical projects by contemporary visual artists who use archives together with photography as documentary and performative media for the comparative study of environments and places. A wide array of artists from diverse backgrounds working primarily in Europe and North America from the 1970s to the present day are discussed and set in relation to Anthropocene narratives. Case studies include environmental archive-based work by Nguyen the Thuc, Christiane Eisler, Chrystel Lebas, Mark Dion, Joy Gregory and Philip Miller. The book will be of interest to scholars working in photography, archive studies, art history, visual culture, environmental humanities, and ecocriticism"--